Effect of 18β-glycyrrhetinic acid on cerebral vasospasm caused by asymmetric dimethylarginine after experimental subarachnoid hemorrhage in rats. (1st June 2015) - Zhao, Dong; Liu, Qi; Ji, Yunxiang; Wang, Ganggang; He, Xuejun; Tian, Weidong; Xu, Hui; Lei, Ting; Wang, Yezhong
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Cerebral vasospasm (CVS) after subarachnoid hemorrhage (SAH) is characterized by the severe constriction of an artery, which often leads to unfavorable outcomes. CVS after SAH is closely associated with asymmetric dimethylarginine (ADMA) and connexin. The effect of 18β-glycyrrhetinic acid (18β-GA), an inhibitor of gap junction, on ADMA, connexin, and CVS after SAH were investigated. Methods: Sprague–Dawley rats (n = 120), weighing 300–350 g, were divided into the control group, sham, SAH, and SAH + 18β-GA groups. In the SAH group, blood was injected into the prechiasmatic cistern of the rats, and 18β-GA (10 mg/kg) was intraperitoneally injected. The neurological score, basilar artery diameter, ADMA, and connexin protein contents (Cx40, Cx43, and Cx45) were measured using Kaoutzanis scoring system, pressure myograph, enzyme linked immunosorbent assay kit, and Western blot, respectively, 1, 3, 5, 7, and 14 days after SAH. Results: The neurological score significantly decreased 3, 5, 7, and 14 days after SAH. The basilar artery diameter significantly decreased, and the ADMA level in the cerebrospinal fluid (CSF) significantly increased at all time points. The level of Cx40 significantly decreased on days 3, 5, 7, and 14, and the level of Cx43 and Cx45 significantly increased at all time points. ADMA and Cx43 are positively correlated. However, the upregulated level of ADMA, Cx43, and Cx45 were attenuated. The neurology result significantly improved in the SAH + 18β-GA group. Conclusions: Treatment with 18β-GA in SAH rats decreases Cx43 and Cx45 in basilar artery and ADMA in CSF. ADMA is probably involved in the pathophysiological events of CVS after SAH by altering connexin proteins. The mechanism of connexin protein changes caused by ADMA needs to be further studied.